Transformations of the Contemporary Catholic Education Discourse: A Thematic Analysis of Church Documents - Labokas, Juozapas (Acta Paedagogica Vilnensia, 2022)
This article analyzes changes in the official teaching of the Catholic Church on education since the late 1920s up to 2013. This is done in order to provide a comprehensive map of the Church‘s educational thought development, and thus facilitate a theoretical and practical discussion on possible ways of further development of the concept. Nine documents used in this analysis were retrieved from the public online database of the Congregation for Catholic Education. The documents in this study are treated as symbolic representations and social facts that make direct or indirect impact on the development of the concept of Christian education, and therefore are significant objects of the analysis. To better elucidate the development of the educational thought, the method of thematic analysis is applied for the content research of the document. Analysis revealed that anhropological shift in Churches‘ thought during the Second Vatican council had effected Churches’ educational thought, but this change was rather evolutionary-incremental than revolutionary-straight-forward.
Keywords: Catholic education; concept of education; Catholic school